Postoperative systemic inflammatory response syndrome predicts increased mortality in patients after elective craniotomy - Peng, Liyuan; Gan, Qi; Xiao, Yangchun; He, Jialing; Cheng, Xin; Wang, Peng; Chen, Lvlin; Li, Tiangui; He, Yan; Chong, Weelic; Hai, Yang; You, Chao; et al. (Frontiers in Surgery, 2024)
Introduction Patients undergoing craniotomy are at high risk of perioperative morbidity and mortality due to excessive inflammatory responses. The purpose of the present study is to evaluate the prognostic utility of postoperative systemic inflammatory response syndrome (SIRS) in patients undergoing craniotomy. Methods We performed a retrospective cohort study of patients who underwent craniotomy between January 2011 and March 2021. SIRS was diagnosed based on two or more criteria (hypo-/hyperthermia, tachypnea, leukopenia/leukocytosis, tachycardia). We used univariate and multivariate analysis for the development of SIRS with postoperative 30-day mortality. Results Of 12,887 patients who underwent craniotomy, more than half of the patients (n = 6,725; 52.2%) developed SIRS within the first 7 days after surgery, and 157 (1.22%) patients died within 30 days after surgery. In multivariable analyses, SIRS (OR, 1.57; 95% CI, 1.12–2.21) was associated with 30-day mortality. Early SIRS was not predictive of 30-day mortality, whereas delayed SIRS was predictive of 30-day mortality. Abnormal white blood cell (WBC) counts contributed the most to the SIRS score, followed by abnormal body temperature, respiratory rate, and heart rate. Conclusion Postoperative SIRS commonly occurs after craniotomy and is an independent predictor of postoperative 30-day mortality. This association was seen only in delayed SIRS but not early SIRS. Moreover, increased WBC counts contributed the most to the SIRS score.